ASSESSMENT OF THE SOCIAL POTENTIAL OF KASHKADARYA REGION AND PRIORITY DIRECTIONS FOR ITS MANAGEMENT - Erkayeva, Gulbakhor Panjiyevna; Zoirov, Golibjon Toshtemir ogli (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical and methodological foundations of assessing the social potential of the regions of Uzbekistan, as well as its practical aspects based on the case of Kashkadarya region. The concept of “social potential” is analyzed from various scientific perspectives, and its structural elements are systematically identified. The study applies an integral assessment method based on indicators such as demographic processes, education, healthcare, employment, income, and infrastructure. The results serve to identify the strengths and weaknesses of the region and contribute to improving social policy.